Pengembangan Sistem Informasi Kepegawaian Berbasis Web pada Kejaksaan Tinggi Sumatera Selatan - Ferradinnie Dwi Hapsari; Sulistiyanto (Journal of Technology and Data Science, 2024)
Personnel data management at the Development Division of the Kejaksaan Tinggi Sumatera Selatan (South Sumatra High Prosecutor's Office) still relies entirely on Microsoft Word-based manual documents, causing delays in data processing and heightened risks of employee information inaccuracies. This study aims to design and develop a web-based personnel information system capable of automating the management of 215 employees, encompassing modules for payroll with nine allowance components, attendance, leave requests, and job transfers. System development followed the Waterfall model across five sequential phases requirements analysis, design, implementation, testing, and maintenance employing PHP 8.1, CodeIgniter 4 MVC framework, and MySQL 8 as the technology stack. Black-Box testing across 38 test scenarios demonstrated 100% functional compliance, System Usability Scale evaluation with 12 respondents yielded a score of 78.3 in the Good category, and average data retrieval response time reached 1.8 seconds. The resulting system contributes a six-table database model with 47 attributes encompassing nine allowance and four deduction components for civil servants, while addressing a literature gap on SIMPEG for Indonesian judicial institutions.